DE-RADICALIZATION OF INTERPRETATION THE CONCEPT OF JIHAD IN TAFSIR AL-QUSYAIRI - M. Minanur Rohman (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2020)
This research tries to raise the interpretation of al-Qusyairi about jihad verses in the Latāif al-Isyārāt. Through content analyctical method, the writer reveals how the substance and the method of interpretation about jihad verses in the Latāif al-Isyārāt and their significance for the definition of de-radicalize the understanding of religious texts. The view of al-Qusyairi against jihad can be concluded into two points. Those are peaceful jihad and armed jihad. The significance of jihad verses in the lathaif al-Isyarat can be seen from the aspect of method and substance. From the aspects of the method, the view of al-Qusyairi becomes important because it has offered an open meaning model, contextual, possible solution, and not one direction. From the substance aspect, al-Qusyairi's view of the verses of jihad confirms that jihad is not revolutionary and radical. The view is quite important to inform the public that the jihad is not only war and violence.